Recent progress in DNA methyltransferase inhibitors as anticancer agents - Zhang, Zhixiong; Wang, Guan; Li, Yuyan; Lei, Dongsheng; Xiang, Jin; Ouyang, Liang; Wang, Yanyan; Yang, Jinliang (Frontiers in Pharmacology, 2022)
DNA methylation mediated by DNA methyltransferase is an important epigenetic process that regulates gene expression in mammals, which plays a key role in silencing certain genes, such as tumor suppressor genes, in cancer, and it has become a promising therapeutic target for cancer treatment. Similar to other epigenetic targets, DNA methyltransferase can also be modulated by chemical agents. Four agents have already been approved to treat hematological cancers. In order to promote the development of a DNA methyltransferase inhibitor as an anti-tumor agent, in the current review, we discuss the relationship between DNA methylation and tumor, the anti-tumor mechanism, the research progress and pharmacological properties of DNA methyltransferase inhibitors, and the future research trend of DNA methyltransferase inhibitors.